Plant community impact on productivity: Trait diversity or key(stone) species effects?. (21st January 2022) - Brun, Philipp; Violle, Cyrille; Mouillot, David; Mouquet, Nicolas; Enquist, Brian J.; Munoz, François; Münkemüller, Tamara; Ostling, Annette; Zimmermann, Niklaus E.; Thuiller, Wilfried
Abstract: Outside controlled experimental plots, the impact of community attributes on primary productivity has rarely been compared to that of individual species. Here, we identified plant species of high importance for productivity (key species) in >29, 000 diverse grassland communities in the European Alps, and compared their effects with those of community‐level measures of functional composition (weighted means, variances, skewness and kurtosis). After accounting for the environment, the five most important key species jointly explained more deviance of productivity than any measure of functional composition alone. Key species were generally tall with high specific leaf areas. By dividing the observations according to distinct habitats, the explanatory power of key species and functional composition increased and key‐species plant types and functional composition‐productivity relationships varied systematically, presumably because of changing interactions and trade‐offs between traits. Our results advocate for a careful consideration of species' individual effects on ecosystem functioning in complement to community‐level measures. Abstract : We identified species of high importance for productivity (key species) in >29, 000 diverse grassland communities in the European Alps, and compared their effects with those of community‐level measures of functional composition. After accounting for the environment, the five most important key species jointly explained more deviance of productivity than any measure of functional composition alone. Our results advocate for a careful consideration of species' individual effects on ecosystem functioning in complement to community‐level measures.